Impact of Lifestyle and Diets Behaviors on Elderly Health: Questionnaire Based Cross-Sectional Study - Tian, Hua; Chen, Jie (Progress in Nutrition, 2022)
Background: Healthy lifestyle and diet behaviors have a great impact on the life of the elderly. Up to now, few objectively evaluate the relationship between the elderly health and related lifestyle behaviors and dietary behaviors from the three dimensions of self-rated health, objective physical health and mental health.Objective: The aim is to understand the elderly health over 65 in CLHLS-2018, the characteristics of participants related to elderly health, and the relationship between elderly health and lifestyle behaviors and dietary behaviors.Methods: 8777 elderly aged over 65 years old was drawn from the Chinese Longitudinal Healthy Longevity Survey (CLHLS-2018). SPSS was used for descriptive statistics of the participants. T-test was used to assess the association between participant characteristics (gender, residence, age, nationality, and living status) and three dimensions of elderly health. Logistic regression analysis was used to assess the relationship between elderly health and lifestyle and diet behavior of the elderly（exercise, social activities, dietary supplements, sleep, drinking, smoking, BMI, staple food, fresh fruit, fresh vegetables and taste）.Results: Among the 8777 participants, the elderly were mainly from female (53.65%), rural(74.30%), 65-79 years old (41.57%), han nationality (95.48%), and living with his/her family or nurses (80.40%). For lifestyle and diet behaviors, the unoptimistic indicators were regular exercise (35.91%), regular social activities (9.71%), regular dietary supplements (12.58%), fresh fruit (23.37%). There were significant differences between the indicators of gender, residence, age and living status. Participants in the healthy group had a healthier lifestyle and diet behaviors than those in the unhealthy group.Conclusions: The elderly health in China is not optimistic. Family members, friends and nurses must be encouraged to provide social support for the elderly in order to carry out more healthier lifestyle and diet behaviors together, which provides a new insight into the study of elderly well-being.